ANALISIS YURIDIS PELAKSANAAN PENGADAAN VAKSIN DALAM PENANGANAN CORONAVIRUS DISEASE 2019 (COVID-19) [A Legal Analysis of the Implementation of Vaccine Procurement in Managing the Coronavirus Disease 19 (Covid-19)] - Lailatul Mufidah; Kukuh Tejomurti (Law Review, 2021)
This article elaborates two legal issues related to how to implement the procurement of the Covid-19 vaccine during a pandemic and the legal responsibility for the implementation of vaccine procurement in the context of handling Covid-19. This article is a prescriptive normative legal research using the statutory approach and the conceptual approach. The study results show that the implementation of procurement for handling emergencies requires a unique mechanism that is carried out through simplification of administrative processes and under Regulation Related to Procurement of Goods/Services in Emergency Management. Article 27 paragraph (2) and section (3) of the Covid-19 Handling Law, which has legal impunity that does not necessarily eliminate the procurement actors' responsibility, but the procurement actors are still subject to legal accountability based on good faith parameters and implementation under regulations legislation. State finances issued in the procurement of the Covid-19 vaccine can be given a temporary conclusion that it has been implemented effectively considering the efficacy level of the Sinovac vaccine is above the minimum percentage given by WHO, namely 65.3% of the minimum amount of 50%Bahasa Indonesia Abstrak: Artikel ini meneliti dua permasalahan hukum terkait bagaimana penerapan pengadaan vaksin Covid-19 di masa pandemi dan pertanggungjawaban hukum atas pelaksanaan pengadaan vaksin yang dilaksanakan dalam rangka penanganan Covid-19. Artikel ini adalah termasuk penelitian hukum yang bersifat preskriptif dengan menggunakan pendekatan peraturan perundang-undangan dan pendekatan konseptual. Hasil penelitian menunjukan bahwa pelaksanaan pengadaan guna penanganan keadaan darurat membutuhkan suatu mekanisme khusus yang mana dilaksanakan melalui penyederhanaan proses administratif dan sesuai regulasi Pengadaan Barang/Jasa dalam Penanganan Keadaan Darurat. Pasal 27 ayat (2) dan ayat (3) UU Penanganan Covid-19 yang memiliki impunitas hukum yang sejatinya tidak serta-merta menghilangkan tanggung jawab para pelaku pengadaan melainkan para pelaku pengadaan tetap dikenai adanya pertanggungjawaban hukum berdasarkan parameter itikad baik dan pelaksanaan yang sesuai dengan peraturan perundang-undangan. Keuangan negara yang dikeluarkan dalam pengadaan vaksin Covid-19 dapat diberikan kesimpulan sementara bahwa telah dilaksanakan secara efektif, mengingat tingkat efikasi vaksin Sinovac berada di atas minimal persentase yang diberikan oleh WHO, yaitu 65,3% dari jumlah minimal 50%.